Debate: The Challenges and Perils of Reframing Trafficking as ‘Modern-Day Slavery’ - Chuang, Janie (Anti-Trafficking Review, 2015)
In the last five years, we have seen a rebranding of global anti-trafficking efforts as ‘modern-day slavery’ abolitionism. The United States of America (US) Department of State and powerful philanthropists are key proponents of the slavery makeover, prompting other governments, international organisations, and non-governmental organisations alike to adopt the ‘modern-day slavery’ frame. The slavery frame has helped ignite outrage and galvanise political support for modern anti-slavery campaigns. It has also helped expand the anti-trafficking spotlight beyond the sex sector to expose the extreme exploitation that men, women, and children suffer in the non-sexual labour sectors of our global economy. These benefits come at a cost, however, both with respect to legal doctrine and practice, and, perhaps more significantly, to how we understand and respond to the problem of extreme exploitation for profit.